12‐3: Organic Light‐emitting Diode Microdisplay with a 32:9 Aspect Ratio for Wide Field of View. Issue 1 (25th September 2020) - Lee, Hyunkoo; Cho, Hyunsu; Byun, Chun-Won; Kang, Chan-mo; Shin, Jin-Wook; Choi, Sukyung; Kwon, Byoung-Hwa; Cho, Nam Sung; Cho, Ara; Kim, Hokwon; Cho, Jeong; Park, Sang Hyun; et al.
Abstract : Microdiplay is one of critical factors to determine the performance of AR glasses. A white OLED with tandem structure have been developed for OLED microdiplays. The device has driving voltage of 6.9 V for 1, 000 cd/m 2 and maximum current efficiency of 19.5 cd/A. Using developed white OLED structure, we have successfully demonstrated a white OLED microdisplay with a 32:9 aspect ratio. This large aspect ratio can be helpful for improving field of view of AR glasses using a pin mirror lens.